Expert consensus on clinical applications of ovarian function suppression for Chinese women with early breast cancer (2024 edition) - Committee of Breast Cancer Society, China Anti-Cancer Association (Zhongguo aizheng zazhi, 2024)
In China, 60% of breast cancer patients were premenopausal women at the time of diagnosis. Compared with postmenopausal women, premenopausal women have strong ovarian function and secrete estrogen to promote breast cancer growth. Ovarian function suppression (OFS) has been used in the treatment of breast cancer for decades, and a large body of evidence-based medical research confirmed that the application of OFS alone or combination therapy can reduce the recurrence risk and improve survival in premenopausal women with breast cancer. The long-term follow-up data of OFS studies have been published successively. SOFT and TEXT study reported the follow-up results of 12 and 13 years, the STO-5 study reported the follow-up data of 20 years, and the ASTRRA study based on Asian populations reported the follow-up data of 8 years. It is further confirmed that the application of OFS for patients with early breast cancer could significantly reduce the recurrence risk over ten years and improve the possibility of cure. MonarchE study and NATALEE study demonstrated that the application of CDK4/6 inhibitors in combination with endocrine therapy and gonadotropin releasing hormone analog (GnRHa) in premenopausal patients with early breast cancer has further improved the survival benefits. Committee of Breast Cancer Society, China Anti-Cancer Association in the field of breast cancer treatment in China jointly discussed and formulated the “Expert consensus on clinical applications of ovarian function suppression for Chinese women with early breast cancer (2024 edition)” based on the “Expert consensus on clinical applications of ovarian function suppression for Chinese women with early breast cancer (2021 edition)”. The consensus recommends that medical castration with GnRHa is the first choice for OFS in premenopausal hormone receptor-positive early breast cancer. CDK4/6 inhibitors in combination with endocrine therapy and GnRHa benefit the premenopausal hormone receptor-positive breast cancer population, including patients with node-positive breast cancer, and patients with node-negative breast cancer who meet one of any criteria (G3, G2 and Ki-67 proliferation index≥20%, G2 and 21-gene assay recurrence score ≥26, G2 and Prosigna PAM50 high risk, G2 and MammaPrint high risk, G2 and EndoPredict high risk). Chemotherapy eligibility (high risk of recurrence) in the 2023 St. Gallen consensus will also be as one of the risk factors to determine whether OFS is applicable for premenopausal hormone receptor positive breast cancer patients. Adjuvant endocrine therapy plan is decided based on the status of ovarian function before chemotherapy for hormone receptor-positive breast cancer. If ovarian protection is considered, GnRHa concurrent chemotherapy is recommended, which does not affect the survival benefit of patients. If ovarian protection is not considered, it is recommended that GnRHa can be used with start of chemotherapy or sequentially after chemotherapy, the latter is more recommended. Endocrine therapy for perimenopausal patients is recommended to refer to the premenopausal regimen. The recommended duration of GnRHa in adjuvant endocrine therapy intermediate- and high-risk patients is 5 years. After 5 years’ endocrine therapy combined with GnRHa, if they are not menopausal and well tolerated, they may consider continuing 2 to 5 years of endocrine therapy combined with GnRHa or using selective estrogen receptor modulators (SERM) alone for 2 to 5 years. Adding GnRHa to the adjuvant treatment regimen is safe and tolerable. It is recommended to fully communicate with patients about the use of the drug and possible adverse events before use. Safety management can improve patient adherence. For patients undergoing medical castration, it is not routinely recommended to monitor estrogen levels during medical castration. However, estrogen testing may be performed for clinical decision making when incomplete ovarian suppression is suspected (including changes in usage such as lack of injection experience by the injection provider, changes in dosage forms, or certain physiological changes that may indicate the recovery of ovarian function, such as symptoms of menopause fluctuating periodically). For premenopausal breast cancer patients, whether hormone receptor-positive or hormone receptor-negative, it is recommended to use GnRHa drugs to protect ovarian function, reduce the risk of premature ovarian failure, and reduce fertility damage. It is recommended to start using GnRHa at least 1 week before chemotherapy, once every 28 d, until 2 weeks after the last dose of chemotherapy. Clinical trials conducted on patients with hormone receptor-positive breast cancer are not recommended to include only postmenopausal people. Premenopausal people under GnRHa application conditions should also be explored to clarify the actual effect of experimental drugs on these patients. In addition, this consensus also adds a full management path for OFS drug application in patients with early/locally advanced breast cancer, in order to further assist clinical decision-making.